Developing an infographic map of the Philippines utilizing the mnemonic attribute of visual emphasis and subornation - Casaclang, Franz Oliver C. (2013)
Visual emphasis is a design principle used to create a focal point in a design; an important principle that helps communicate a message of a given design. It was proposed in the research that through the power of today?s multimedia technology to potentially apply visual emphasis in learning materials, retention of the information the material contains would be higher for its users. Summarizing what emphasis and subordination could contribute to visual learning, aside from creating a focal point in a design is that: 1.) it contributes to the early stages of perception, 2.) perceptual salience and 3.) it contributes to memory phenomena through attention. It?s a truly ?unforgettable? experience to a Filipino elementary student, dealing with 7,107 islands, which consists of 17 regions and 80 provinces plus the cities. Most of that experience is spent dealing with the dreaded Philippine map. You could be a little unfortunate if you don?t have the fancy colored ones, but it?s not exactly a favorable situation. These maps are most of the time a ?sea of words?, trying to put as much information as possible in every inch of the area of the paper. The problem focused on how the mnemonic attribute of visual emphasis and subordination could be utilized to create a better material that will aid the student in studying effective experience for the target studying Philippine geography, the creation of a digital Philippine map application (applying the concepts from research) was then proposed.